A Systematic Review of Sources of Outcomes and Cost Data Utilized in Economic Evaluation Research Conducted in the Gulf Cooperation Council - AlAujan SS; Almazrou SH; Al-Aqeel SA (Dove Medical Press, 2021)
Shiekha S AlAujan, Saja H Almazrou, Sinaa A Al-Aqeel Clinical Pharmacy Department, College of Pharmacy, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Shiekha S AlAujanClinical Pharmacy Department, College of Pharmacy, King Saud University, Riyadh, Saudi ArabiaEmail salaujan@ksu.edu.saBackground: Transparency and clarity in reporting of methods used to identify, measure, and value outcomes and resources in published economic evaluations is crucial.Objective: The aims of this review were to identify and assess the quality of published economic evaluation studies in the Gulf Cooperation Council (GCC) region, with a specific focus on methods used to identify, measure, and value cost and outcomes data.Methods: An electronic search of publications from 2009 to October 2019 was performed in three clinical (Medline, Scopus, and EMBASE) and one economic (NHS EED) databases. Full economic evaluations undertaken in GCC countries from any perspective were included. Reference lists of three reviews on the same topic and area were also searched for further eligible articles. The Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist was used for methodological quality assessment. Data on type and source of cost and outcomes data were collected.Results: Out of 1857 studies identified, 14 relevant studies were eligible and included. Eleven studies were based in Saudi Arabia, and the remaining studies were published in the United Arab of Emirates (UAE), Qatar, and Oman. Majority of the evaluations were based on the Markov modelling (n=8). None of the studies fully fulfilled the CHEERS quality criteria. Quality-adjusted life years (QALYs) was the main outcome (n=10). The EQ-5D was valued using the UK value set tariff (n=6). Published literature was the source of outcomes data in seven studies. Hospital-based data were used as a source of healthcare resource use data in four studies, whereas hospital-based costs (n = 7) combined with other sources such as local/national data were the sources of unit cost data in the majority of the studies.Conclusion: Rigorous economic evaluations are lacking in the region leading to inaccurate information being given to decision-makers.Keywords: economics evaluation, cost-effectiveness analysis, cost analysis, Gulf Cooperation Council